Cells respond to mechanical stress by rapid disassembly of caveolae - Sinha, Bidisha; Köster, Darius; Ruez, Richard; Gonnord, Pauline; Bastiani, Michele; Abankwa, Daniel; Stan, Radu V; Butler-Browne, Gillian; Vedie, Benoit; Johannes, Ludger; Morone, Nobuhiro; Parton, Robert G; et al. (Cell, 2011)
The functions of caveolae, the characteristic plasma membrane invaginations, remain debated. Their abundance in cells experiencing mechanical stress led us to investigate their role in membrane-mediated mechanical response. Acute mechanical stress induced by osmotic swelling or by uniaxial stretching results in a rapid disappearance of caveolae, in a reduced caveolin/Cavin1 interaction, and in an increase of free caveolins at the plasma membrane. Tether-pulling force measurements in cells and in plasma membrane spheres demonstrate that caveola flattening and disassembly is the primary actin- and ATP-independent cell response that buffers membrane tension surges during mechanical stress. Conversely, stress release leads to complete caveola reassembly in an actin- and ATP-dependent process. The absence of a functional caveola reservoir in myotubes from muscular dystrophic patients enhanced membrane fragility under mechanical stress. Our findings support a new role for caveolae as a physiological membrane reservoir that quickly accommodates sudden and acute mechanical stresses.